Analysis of Spending Performance in the Budget Realization Report (LRA) in Deli Serdang Regency - Waldani, Anggi Jumiafitri; Siregar, Annisa Ramadhani; Buulolo, Meriana; Sasmita, Puteri Keshya Adisty; Chrisna, Heriyati (Lembaga Riset Mutiara Akbar, 2024)
Deli Serdang Regency, as one of the regions with significant economic growth in North Sumatra Province, has an important role in regional development. To achieve the established development goals, effective and efficient regional financial management is needed. One of the important instruments in regional financial management is the Budget Realization Report (LRA). This study aims to analyze spending performance in the Budget Realization Report (LRA) in Deli Serdang Regency. With significant economic growth, effective and efficient regional financial management is needed to achieve the established development goals. LRA serves as a tool for transparency and accountability in the use of public budgets. This study uses quantitative data from the 2019-2022 fiscal year LRA, focusing on spending variance analysis and spending growth analysis. The results of the study show that there is a significant difference between the planned budget and the realization of spending, with challenges in financial management faced. These findings are expected to provide insight to improve the effectiveness and efficiency of regional budget management in the future.